Aquaglyceroporin Modulators as Emergent Pharmacological Molecules for Human Diseases - Pimpão, Catarina; Wragg, Darren; da Silva, Inês V.; Casini, Angela; Soveral, Graça (Frontiers in Molecular Biosciences, 2022)
Aquaglyceroporins, a sub-class of aquaporins that facilitate the diffusion of water, glycerol and other small uncharged solutes across cell membranes, have been recognized for their important role in human physiology and their involvement in multiple disorders, mostly related to disturbed energy homeostasis. Aquaglyceroporins dysfunction in a variety of pathological conditions highlighted their targeting as novel therapeutic strategies, boosting the search for potent and selective modulators with pharmacological properties. The identification of selective inhibitors with potential clinical applications has been challenging, relying on accurate assays to measure membrane glycerol permeability and validate effective functional blockers. Additionally, biologicals such as hormones and natural compounds have been revealed as alternative strategies to modulate aquaglyceroporins via their gene and protein expression. This review summarizes the current knowledge of aquaglyceroporins' involvement in several pathologies and the experimental approaches used to evaluate glycerol permeability and aquaglyceroporin modulation. In addition, we provide an update on aquaglyceroporins modulators reported to impact disease, unveiling aquaglyceroporin pharmacological targeting as a promising approach for innovative therapeutics.